2007
DOI: 10.1105/tpc.106.045427
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Chloroplast Nucleic Acid Metabolism into the Phosphate Deprivation Response in Chlamydomonas reinhardtii

Abstract: Cell survival depends on the cell's ability to acclimate to phosphorus (P) limitation. We studied the chloroplast ribonuclease polynucleotide phosphorylase (PNPase), which consumes and generates phosphate, by comparing wild-type Chlamydomonas reinhardtii cells with strains with reduced PNPase expression. In the wild type, chloroplast RNA (cpRNA) accumulates under P limitation, correlating with reduced PNPase expression. PNPase-deficient strains do not exhibit cpRNA variation under these conditions, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 88 publications
2
64
0
Order By: Relevance
“…However, subsequent isolation and analysis of longer tails revealed that although rich in adenosines, most of the tails contained other nucleotides, suggesting that the tails in Chlamydomonas chloroplasts are often heteropolymeric (see below and Figure S3). As mentioned earlier, Chlamydomonas appears to encode a single, chloroplast PNPase (Yehudai-Resheff et al, 2007), although a dual targeting to mitochondria has not been excluded. In order to analyze the possible involvement of PNPase and CrPAP4 in the polyadenylation of chloroplast or mitochondrial transcripts, we used RNAi to reduce expression of these enzymes and analyzed the tail composition in the resultant strains.…”
Section: Polynucleotide Phosphorylase May Be Largely Responsible For mentioning
confidence: 99%
See 3 more Smart Citations
“…However, subsequent isolation and analysis of longer tails revealed that although rich in adenosines, most of the tails contained other nucleotides, suggesting that the tails in Chlamydomonas chloroplasts are often heteropolymeric (see below and Figure S3). As mentioned earlier, Chlamydomonas appears to encode a single, chloroplast PNPase (Yehudai-Resheff et al, 2007), although a dual targeting to mitochondria has not been excluded. In order to analyze the possible involvement of PNPase and CrPAP4 in the polyadenylation of chloroplast or mitochondrial transcripts, we used RNAi to reduce expression of these enzymes and analyzed the tail composition in the resultant strains.…”
Section: Polynucleotide Phosphorylase May Be Largely Responsible For mentioning
confidence: 99%
“…In order to analyze the possible involvement of PNPase and CrPAP4 in the polyadenylation of chloroplast or mitochondrial transcripts, we used RNAi to reduce expression of these enzymes and analyzed the tail composition in the resultant strains. The generation of a stable PNPasedepleted strain PNPi3 (also called ip3; with a reduction in the protein amount of approximately 90%) has been previously described (Yehudai-Resheff et al, 2007), and an analogous strain, PAP4i, was obtained for CrPAP4 ( Figures S1 and S2).…”
Section: Polynucleotide Phosphorylase May Be Largely Responsible For mentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Under phosphate-limiting conditions, chloroplast DNA was reportedly degraded in Chlamydomonas, possibly as a compensation mechanism for survival. 8 Furthermore, the characterization of plastidial uracil phosphoribosyltransferases showed that plastid functions as the…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%